An Alternative View of the Ukrainian Conflict: Stephen F. Cohen on the Origins of the New Cold War. Issue 1 (2nd January 2023) - Gaido, Daniel
ABSTRACT: This article deals with views of the American scholar of Russian studies Stephen F. Cohen (1928–2020) on what he termed the "new Cold War"—i.e., the confrontation between the United States and Russia brought about by the US-driven expansion of NATO to Eastern Europe. Given the topicality of Cohen's views for the analysis of the current war in Ukraine, this article offers a summary and critical assessment of Cohen's analyses and of his warnings about the potential consequences of US foreign policy in Europe. The conclusion is that Cohen's analysis was vindicated by the outbreak of the current war in Ukraine, but that his "Russo-centric" view is too narrow, and that his analysis must be placed in the larger global context within which the war in Ukraine takes place: US imperialism's two-pronged aggression against both Russia and China.